The Adventitia: A Dynamic Interface Containing Resident Progenitor Cells - Majesky, Mark W. (2011)
Conventional views of the tunica adventitia as a poorly organized layer of vessel wall composed of fibroblasts, connective tissue and perivascular nerves are undergoing revision. Recent studies suggest that the adventitia has properties of a stem/progenitor cell niche in the artery wall that may be poised to respond to arterial injury. It is also a major site of immune surveillance and inflammatory cell trafficking, and harbors a dynamic microvasculature, the vasa vasorum, that maintains the medial layer and provides an important gateway for macrophage and leukocyte migration into the intima. In addition, the adventitia is in contact with tissue that surrounds the vessel and may actively participate in exchange of signals and cells between the vessel wall and the tissue in which it resides. This brief review highlights recent advances in our understanding of the adventitia and its resident progenitor cells and discusses progress toward an integrated view of adventitial function in vascular development, repair and disease.